Nanostructures and Nanomaterials - Cao, Guozhong; Wang, Ying (New Jersey : W S P, 2011)
Focuses on the synthesis and fabrication of nanostructures and nanomaterials and includes properties and applications of nanostructures and nanomaterials, particularly inorganic nanomaterials. This book provides balanced and comprehensive coverage of the fundamentals and processing techniques with regard to synthesis of nanostructures.
Includes References 546-560p.; Appendix 561-568p.; Index 569-581p.
Keywords: Nanomaterials; Nanotechnology; Physics